Rescue me - Alfonsi, Alice (New York Disney Press Volo, 2004)
Raven has a date with a high school boy, even though her parents don't approve. But when she sneaks out for what proves to be the world's worst date, how can she escape without her parents finding out?
"Based on the series created by Michael Poryes, Susan Sherman; part one is based on the teleplay written by Dava Savel ; part two is based on the teleplay written by Bob Keyes & Doug Keyes."
"From the hit TV series on Disney Channel"--Cover
2
Keywords: Dating (Social customs) -- Juvenile fiction; Junior high school students -- Juvenile fiction; Schools -- Juvenile fiction; Dating (Social customs) -- Fiction; Junior high school students -- Fiction; Schools -- Fiction; San Francisco (Calif.) -- Juvenile fiction; San Francisco (Calif.) -- Fiction